2015
DOI: 10.1159/000379757
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Proactive Psychiatric Consultation Service: Impact on Length of Stay for Medical Inpatients

Abstract: Background: Mental illness correlates with an increased length of stay (LOS) for patients hospitalized for medical conditions. While psychiatric consultations help manage mental illness among those hospitalized for medical conditions, consultations initiated by nonpsychiatric mental disease may lack maximum effectiveness. Methods: In a before-and-after design, in 2 contiguous years LOS for internist-initiated, conventional consultation (CC) as usual treatment was compared to LOS of a proactive, mental health p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…The studies by Orsak and colleagues (25) and Sledge and colleagues (26) evaluated proactive psychiatric consult liaison services in two different academic medical centers. In the study by Orsak, the intervention occurred on two hospitalist teams, and outcomes were compared to three hospitalist teams who continued to consult psychiatry in the traditional fashion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies by Orsak and colleagues (25) and Sledge and colleagues (26) evaluated proactive psychiatric consult liaison services in two different academic medical centers. In the study by Orsak, the intervention occurred on two hospitalist teams, and outcomes were compared to three hospitalist teams who continued to consult psychiatry in the traditional fashion.…”
Section: Resultsmentioning
confidence: 99%
“…Proactive psychiatric consultation, as studied by Orsak (25) and Sledge (26), may be able reduce psychotropic medication errors and delays, reduce agitation, and improve coordination with outpatient mental health providers, as proactive consultation has been found to reduce inpatient length of stay (26,45). Screening patients for depression or other mental health symptoms with validated tools during the inpatient hospital course, as studied by Jennings (27) and Huffman (34,35), also holds value.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the LOS was reduced by 23.7% (9 days) in the pilot study of Desan et al conducted in the United States . Furthermore, it has also been shown that people receiving a proactive psychiatric consultation compared to the conventional liaison service had a significantly shorter hospitalization . Another approach to improve care for PWD hospitalized for acute somatic illness could be special care units …”
Section: Discussionmentioning
confidence: 99%
“…77 Furthermore, it has also been shown that people receiving a proactive psychiatric consultation compared to the conventional liaison service had a significantly shorter hospitalization. 78 Another approach to improve care for PWD hospitalized for acute somatic illness could be special care units. 79 An additional explanation for a longer LOS among PWD may be the functional and cognitive decline during hospitalization, 80 which could prevent PWD from expressing their complaints to the medical staff including the occurrence of adverse drug reactions 31,[81][82][83] occurring in up to 11% of the hospital admissions.…”
Section: Los In Hospitalizations Due To Infectious Cardiovascularmentioning
confidence: 99%
“…Specific geriatric and pediatric psychiatric consultation services are also available [211,212]. The existing literature indicates that the goals of consultation-liaison psychiatry (reducing the length of hospitalization and utilization of laboratory tests, providing an input on patient management, and improving social functioning after discharge) can be met, even though results considerably differ across studies [210,213,214]. Developments of consultation-liaison psychiatry are hindered by its modalities of assessment and treatment that follow a reductionist (psychiatric) paradigm, missing psychosocial perspectives and correlates that may affect the response to medical treatments [215,216].…”
Section: Multidisciplinary Carementioning
confidence: 99%